Mastering javascript design patterns : discover how to use JavaScript design patterns to create powerful applications with reliable and maintainable code - Timms, Simon (Birmingham, UK : Packt Publishing, Limited, 2014)
Applying design patterns to JavaScript code creates more reliable and maintainable code. In this book, you will explore different design patterns and learn where and how to implement them with the help of detailed examples. In the first part of the book, we start off with an introduction to design patterns, and then move on to creating classical structures that are used to organize code. Next, we look at the creational, structural, and behavioral patterns. The second part of the book dives into patterns used for functional programming, model view patterns, patterns to build web applications, and messaging patterns. A number of very interesting advanced JavaScript patterns such as dependency injection and live postprocessing are also covered. By the end of this book, you will learn to identify places where a pattern would improve code readability and maintainability.
1. Designing for fun and profit -- Part 1. Classical design patterns -- 2. Organizing code -- 3. Creational patterns -- 4. Structural patterns -- 5. Behavioral patterns -- Part 2. Other patterns -- 6. Functional programming -- 7.Model view patterns -- 8. Web patterns -- 9. Messaging patterns -- 10. Patterns for testing -- 11. Advanced patterns -- 12. ES6 solutions today.
Includes index.
Keywords: JAVASCRIPT (COMPUTER PROGRAM LANGUAGE)